Routing Algorithm of Mobile Agents for Query Retrieval Using Genetic Algorithm - Selamat, Ali; Selamat, Md. Hafiz (Malaysian Journal of Computer Science, 2004)
Mobile agents often have a task to collect data from several predefined sites. This should be done in an efficient way by minimising the elapsed time. Usually these agents only know the list of sites but not the distances between them. This paper proposes a method to minimise a network routing time taken by the mobile agents to collect information from different sites using genetic algorithm (GA). The mobile agents repeat travelling over short routes and avoid longer ones. Mobile agents for query retrieval have used the GA to select the best routes that minimise the query retrieval time. The result shows that the proposed method provides good time minimisation in retrieving the query results by the mobile agents based on different GA parameters.